(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The purpose of preparing the review manuscript is to highlight the importance of the physical specifications of the most important of inorganic fillers such as "carbon black" and "silica" that have good physical specifications as surface area, particle size distribution and surface chemistry. Moreover, study the effect of these specifications on the resistance of vulcanized rubber compound for swelling, which is one of the disadvantages to determine the expansion of its uses in industrial applications through the review of many types of research in this area. The results proved that there is a strong relationship between the curing characteristics of the rubber compound such as the time of curing, the scorch time in addition to the "curing rate index’ (CRI) and mechanical properties especially the tensile strength and "density of cross-links" for reducing the swelling rate to the minimum. By increasing the "density of cross-links" and improve the specifications of vulcanization and mechanical specifications.